2018
DOI: 10.1177/2325967118794367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of KD3-M and KD3-L Multiligamentous Knee Injuries and Analysis of Predictive Factors That Influence the Outcomes of Single-Stage Reconstruction in KD3 Injuries

Abstract: Background:The knee dislocation–3 (KD3) injury pattern is the most common form of multiligamentous injury. Medial KD3 (KD3-M) and lateral KD3 (KD3-L) are 2 anatomically different varieties of this injury.Purpose:To compare the surgical outcomes of KD3-M and KD3-L multiligamentous knee injury patterns and to determine the factors that could influence the outcomes after single-stage reconstruction.Study Design:Cohort study; Level of evidence, 3.Methods:A cohort of 45 patients with multiligamentous knee injuries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…10 In other populations, injury to three ligaments has been identified as the most common injury pattern with KDIII-M and KDIII-L constituting 52.4 and 28.1% of injuries, respectively. 2,4 This finding supports previous literature that indicated MLKI were more commonly associated with medial-sided ligament injuries. 20 KDI injuries were the most frequent injury in our cohort (52%), followed by KDIII (44%) (►Table 1).…”
Section: Injury Patternsupporting
confidence: 90%
See 3 more Smart Citations
“…10 In other populations, injury to three ligaments has been identified as the most common injury pattern with KDIII-M and KDIII-L constituting 52.4 and 28.1% of injuries, respectively. 2,4 This finding supports previous literature that indicated MLKI were more commonly associated with medial-sided ligament injuries. 20 KDI injuries were the most frequent injury in our cohort (52%), followed by KDIII (44%) (►Table 1).…”
Section: Injury Patternsupporting
confidence: 90%
“…4 The Schenck classification defines the severity of injury based on the injured ligaments involved (►Table 2), while the Kennedy classification is based on the direction of displacement of the tibia. 2,4,11…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…** Of these studies, 8 out of 9 reported a prevalence that was in the range of 28.2% to 66.7%. 4,8,12,17,22,32,33,35 One study reported meniscal tears in 15 of 17 patients (88%). 15 Thirteen studies reported having performed a reconstruction of all torn ligaments, yy while 1 study reported on ligament repairs of all injured ligaments 15 and another reported on repair versus reconstruction of the fibular collateral ligament and posterolateral corner.…”
Section: Resultsmentioning
confidence: 99%